Implementation Green Software Engineering Approach in University Course Timetabling Problem - Adilah, Imamah; Setiawan, Dimas Ari; Fatchurrochman, Fatchurrochman (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.654, 2017)
Rapid technological developments have an impact on resources. This allows resources to decrease gradually. Green Computing provides solutions to reduce the impact of technology on resources. One way is to apply green software to the lecture scheduling software that previously spent 45 minutes. Green software will optimize the software both in time and energy. This optimization can be done by choosing the right method, the reduction of looping and the use of data structure. Based on the results of the research found that by using these ways can make the software finish the program quickly which is in the range of 16-20 seconds with different databases. This can save the electrical energy generated from the computer so as to reduce damage to existing natural resources.